Respuestas

¡La mejor respuesta!
2012-06-24T09:24:58+02:00

comensemos:


 ∫senx  dx  

  (cosx)^3

 

cambio de variable:

 

u=cosx

 

aplicanco diferencial:

 

d(u)=d(cosx)

du=-senx dx

senx dx = -du

 

remplazando:

 

 ∫-du  

  u^3

 

-∫du  

  u^3

 

-∫u^(-3)du  

 

-u^(-3+1)

    -3+1

 

 -u^(-2) 

     -2

 

cancelan los (-)

 

u^(-2)

   2

 

cambiando otra vez la variables u= cosx

 

(cosx)^(-2)

     2

 

un gusto....=D

2012-06-24T11:41:57+02:00

si es cos x^3 no (cos x)^3, no es posible a resolver